POLICY ANALYSIS ON STUNTING REDUCTION AND ITS IMPACT ON ECONOMIC DEVELOPMENT IN SIKKA REGENCY - Syahbanda, Samsul Hidayat; Tameno , Nikson; Theresia, Novi (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
The objective of this study is to examine the stunting reduction policy and its challenges in relation to economic development in Sikka Regency. The research method used is descriptive qualitative. The findings show that the implementation of the stunting reduction policy includes programs such as the "Pripong Abong" Adolescent Posyandu, the Foster Parents Movement, and the "Lepo Gahar Naha Blisa" or stunting recovery house. These initiatives involve multiple stakeholders and go through several critical stages, including engagement from governmental and non-governmental organizations as well as the community as the main target group. The policy is designed to reduce stunting prevalence through programs outlined in the Sikka Regency Regent Regulation, focusing on nutritional interventions, improved healthcare services, and community education as key aspects. The provision of financial resource support to the community has positively impacted the implementation of the policy, which has generally been proceeding well. However, there are several challenges to implementing the stunting reduction policy and its contribution to economic development in Sikka Regency. High levels of isolation result in limited access to essential services such as healthcare and education, which increases the community's vulnerability to poverty and underdevelopment. Poor road access to Posyandu centers poses another obstacle for community members to participate in government programs. Furthermore, strong belief in myths and traditional practices among residents hinders the effective implementation of stunting prevention efforts in the region.